DENEYSEL NONALKOLİK STEATOHEPATİT MODELİNDE GENİSTEİNİN KORUYUCU ROLÜ - YALNIZ, MEHMET (Fırat Üniveristesi, 2005)
Oksidatif stres nonalkolik steatohepatit (NASH) patogenezinde rol alan enönemli faktörlerden biridir. Birçok farmakolojik özelliklere sahip bir fitoöstrojenolan genisteinin (4',5, 7-trihydoxyisoflavone) antioksidan ve anti-inflammatuvarHWNLOHUL ROGXÃ·X ELOLQPHNWHGLU %X oDOÃ•ÃºPDGD GHQH\VHO RODUDN ROXÃºWXUXODQ 1$6+PRGHOLQGHJHQLVWHLQLQNRUX\XFXUROÂ QÂ DUDÃºWÃ•UGÃ•N48 adet erkek Sprague-Dawley rat randomize olarak dört HÃºLW JUXED D\UÃ•OGÃ•%LULQFLJUXSVDGHFHVWDQGDUWUDW \HPLDOGÃ•NRQWUROJUXEXJUXS.*UXSSODVHERVHUXPIL]\RORMLNJUXEXJUXSYHÂ¶HLVH\DÃ·GDQ]HQJLQGL\HW<='DGOLELWXPRODUDNYHULOGL*UXSÂ¶H<='Â¶HEDÃºODPDGDQELUJÂ Q|QFHYHWÂ PGHQH\süresince 0.2PJNJJÂ Q GR]XQGD JHQLVWHLQ VXENXWDQ RODUDN X\JXODQGÃ• JHQLVWHLQ NRUX\XFX *.grup). Grup 4'e dördüncü haftadan sonra iki hafta 0.2 mg/kg/gün dozunda genisteinVXENXWDQRODUDNX\JXODQGÃ•JHQLVWHLQWHGDYL*7JUXEXKDIWDELWWLNWHQVRQUDtümUDWODU |OGÂ UÂ OGÂ .DQ |UQHNOHUL YH NDUDFLÃ·HU GRNXODUÃ• DOÃ•QGÃ• $PLQRWUDQVIHUD]ODUSOD]PDYHNDUDFLÃ·HUPDORQGLDOGHKLG0'$GÂ ]H\OHUL|OoÂ OGÂ +LVWRSDWRORMLNRODUDNNDUDFLÃ·HUGHVWHDWR]EDORQODÃºPDGHMHQHUDV\RQXLQIODPPDV\RQ0DOORU\FLVLPFLÃ·LYHfibro]LVGHÃ·HUOHQGLULOGL$67 YH $/7 GHÃ·HUOHUL S SOD]PD YH NDUDFLÃ·HU 0'$ YH SOD]PDTNF-DOID GÂ ]H\OHUL S VÃ•UDVÃ• LOH SODVHER JUXEXQGD NRQWUROgrubundan yüksekti. TGF-EHWD GÂ ]H\OHULQGH DQODPOÃ• IDUN \RNWX +LVWRSDWRORMLNolarak steatoz, mm2 GHNL RUWDODPD LQIODPDWXYDU KÂ FUH VD\Ã•VÃ• YH EDORQODÃºPDGHMHQHUDV\RQX SODVHER JUXEXQGD NRQWURO JUXEXQD J|UH DQODPOÃ• RODUDN \Â NVHNWL SKHSVLQGH )LEUR]LV YH 0DOORU\ FLVPL VDSWDQPDGÃ• +HP *. KHP GH *7grubunda AST ve ALT düzeyleri (p hepsinGH SOD]PD YH NDUDFLÃ·HU 0'$düzeyleri ve TNF-DOID GÂ ]H\OHUL SODVHER JUXEXQD J|UH DQODPOÃ• RODUDN GÂ ÃºÂ NWÂ SKHSVLQGH+LVWRSDWRORMLNLQFHOHPHGH*.YH*7JUXSODUÃ•QGDVWHDWR]VÃ•UDVÃ•LOHp<0.05 ve <0.01), mm2 deki ortalama inflamatuvar hücre sayÃ•VÃ• KHU LNL JUXSWDS YH EDORQODÃºPD GHMHQHUDV\RQX KHU LNL JUXSWD SODVHER JUXEXQD J|UHDQODPOÃ•RODUDNGÂ ÃºÂ NWÂ Sonuç: *Â oOÂ ELU DQWLRNVLGDQ RODQ JHQLVWHLQ GHQH\VHO RODUDN 1$6+ JHOLÃºLPLQLbelirgin olarak önlemekte, histopatolojik ve biyokimyasal düzelme ile steatohepatitiD]DOWPDNWDGÃ•UAnahtar kelimeler: 1RQDONROLN VWHDWRKHSDWLW \DÃ·GDQ ]HQJLQ GL\HW RNVLGDWLI VWUHVgenistein.

Oxidative stress is one of the important factors that are playing role in thepathogenesis of nonalcoholic steatohepatitis (NASH). Genistein (4?,5, 7-trihydoxyisoflavone), a phytoestrogen with several pharmacological features, hasalso antioxidant and anti-inflammatuar properties. In the present study, we evaluatedpreventive role of genistein in NASH model induced experimentally.48 Sprague-Dawley rats were divided into four equal groups randomly. Firstgroup received only standart rat chow diet (control group: grup C). Group 2 (groupplacebo), 3 and 4 were given high fat diet (HFD) ad libitum. 0.5 ml serumphysiologic injected daily to placebo group subcutaneously. 0.2 mg/kg/day genisteininjected subcutaneously to group 3 (genistein prevention (GP) group) starting oneday before HFD administration and during the whole experiment. After the fourthweek, genistein at 0.2 mg/kg/day injected subcutaneously to the fourth group(genistein treatment (GT) group). All rats killed after six weeks. Blood samplescollected and tissue samples prepared. Aminotransferases, plasma and livermalondialdehyde (MDA) levels were measured. Steatosis, ballooning degeneration,inflammation, Mallory body and fibrosis in the liver examined histopathologically.AST and ALT levels (p for each <0.001), plasma and liver tissue MDA andplasma TNF-alpha levels (p <0.001, <0.001, <0.01, respectively) were higher inplacebo group than in the control group. TGF-beta levels were comparable in theplacebo and control groups. In histopthological examination, steatosis, inflammatuarcells per mm2 and balloning degeneration were significantly higher in the placebogroup than in the control group (p for each <0.001). There was no fibrosis andMallory body. AST and ALT levels (p for each <0.05), plasma and liver tissueMDA and plasma TNF-alpha levels were significantly lower (p <0.05 for each)either in GP or in GT groups compared to the placebo group. Histopathologically,steatosis (p<0.05 and <0.01 respectively), mean number of inflammatuar cells permm2 (p<0.01 for each) and balloning degeneration (p <0.01 for each) in GP and GTgroups were significantly lower than in the placebo group.In conclusion; genistein, a strong antioxidant agent, not only remarkablyprevents the emergence of NASH, but also attenuates the existing steatohepatitis byimproving the biochemical and histopathological abnormalities.Key words: Nonalcoholic steatohepatitis, high fat diet, oxidative stress, genistein.
Preventive role of genistein in experimental non-alcoholic steatohepatitis model
Keywords: Gastroenteroloji